2021
DOI: 10.3390/ijms22094659
|View full text |Cite
|
Sign up to set email alerts
|

MIR172d Is Required for Floral Organ Identity and Number in Tomato

Abstract: MicroRNA172 (miR172) functions as a central regulator of flowering time and flower development by post-transcriptional repression of APETALA2-LIKE transcription factors. In the model crop Solanum lycopersicum (tomato), the miR172 family is still poorly annotated and information about the functions of specific members is lacking. Here, de-novo prediction of tomato miR172 coding loci identified seven genes (SlMIR172a-g), that code for four unique species of miR172 (sly-miR172). During reproductive development, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…In flowers expressing a miR172-resistant version of AP2/TOE or with reduced miR172 activity, the stamens were partially (or completely) converted into petals [ 14 , 27 ]. In tomato, miR172c and miR172d seem the most abundant forms in developing flowers [ 31 ], as also observed in peach [ 28 ]. CRISPR-Cas9-editing of tomato miR172c and miR172d showed that hypomorphic and loss-of-function alleles of mir172d were associated with the conversion of petals and stamens to sepaloids, suggesting a dose-dependent regulation of floral organ identity and number [ 31 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In flowers expressing a miR172-resistant version of AP2/TOE or with reduced miR172 activity, the stamens were partially (or completely) converted into petals [ 14 , 27 ]. In tomato, miR172c and miR172d seem the most abundant forms in developing flowers [ 31 ], as also observed in peach [ 28 ]. CRISPR-Cas9-editing of tomato miR172c and miR172d showed that hypomorphic and loss-of-function alleles of mir172d were associated with the conversion of petals and stamens to sepaloids, suggesting a dose-dependent regulation of floral organ identity and number [ 31 ].…”
Section: Discussionmentioning
confidence: 86%
“…In tomato, miR172c and miR172d seem the most abundant forms in developing flowers [ 31 ], as also observed in peach [ 28 ]. CRISPR-Cas9-editing of tomato miR172c and miR172d showed that hypomorphic and loss-of-function alleles of mir172d were associated with the conversion of petals and stamens to sepaloids, suggesting a dose-dependent regulation of floral organ identity and number [ 31 ]. A very recent association study on 417 peach accessions from the Peach Germplasm Repository of Shandong (Agricultural University, China) also suggests the presence of two independent insertion events (named Hap2 and Hap3 ) within the promoter of Prupe.2G237700 [ 32 ] in DF accessions.…”
Section: Discussionmentioning
confidence: 86%
“…Compared with the employment of CRISPR/Cas in the modification of protein-coding genes [6,10,30], the applications of gene editing tools to the modification of noncoding genes are limited and only the simplest strategy, knockout based on CRISPR/Cas systems, has been employed (Table S3). Until recently, our understanding of the utilization of CRISPR/Cas in miRNA coding genes has been restricted to plant species, including M. polymorpha [28,92], arabidopsis [12,13,80], rice [14,15,17,80], wheat [93], soybean [94,95], and tomato [20,90] (Table S3). In addition, miRNAs have been considered as targets for crop improvement against abiotic and biotic stresses [1]; however, further study on the application of CRISPR-based technologies and functional analysis on miRNAs is necessary before this technology can be routinely applied to the targeting of MIR genes in crops.…”
Section: The Potential Application Of Crispr/cas Systems In Mirna Res...mentioning
confidence: 99%
“…The CRISPR/Cas system is an advanced technology for gene editing based on endonucleases, which has revolutionized biotechnology in life sciences, medical sciences, and agriculture [6,7]. Due to the high efficiency and cost-effectiveness of CRISPR/Cas systems [8][9][10][11], they are now widely employed in gene editing of arabidopsis (Arabidopsis thaliana) [12,13] and many important crops such as rice (Oryza sativa) [14][15][16][17][18], tomato (Solanum lycopersicum) [19,20], maize (Zea mays) [21,22], wheat (Triticum aestivum) [23], cotton (Gossypium hirsutum) [24][25][26], and potato (Solanum tuberosum) [27], as well as early-divergent land plants such as the liverwort, Marchantia polymorpha [28], and the model moss, Physcomitrium patens [29]. In addition to gene editing, an increasing number of reports reveal that CRISPR/Cas systems are also being widely employed in base editing, gene regulation, epigenetic editing, chromatin engineering, and imaging [30,31].…”
mentioning
confidence: 99%
“…There are eight SlMIR172 genes in the tomato genome ( Table S2 ) which code for five mature sly-miR172 species, including one that is identical to Arabidopsis miR172a and miR172b and is coded by SlMIR172a / b / e /g ( Table S2 #242, #274, #457, and #484). Degradome analyses indicated that the euphyllophyte APETALA2 transcription factors encoding transcripts SlAP2b ( Solyc02g064960 ), SlAP2c ( Solyc02g093150 ), SlAP2a ( Solyc03g044300 ), Solyc04g049800 , SlAP2e ( Solyc06g075510 ), Solyc09g007260 , Solyc10g084340 , and SlAP2d ( Solyc11g072600 ) undergo miR172-guided cleavage in flowers and developing and ripening fruit pericarp [ 37 , 94 ]. In tomato, sly-miR172c and sly-miR172d seem the most abundant forms in developing flowers, whereas sly-miR172a/b/e/g is more prevalent in developing and ripening fruits [ 94 ].…”
Section: The Functions Of Tomato Mirnasmentioning
confidence: 99%